The various effect of social isolation on depression risk among old population in China during covid-19 pandemic: A population based survey - Zhenjie Wang; Yongai Jin; Wanning Tian; Xun Zhou (PLoS ONE, 2025)
Background The aim of the current study is to assess various effect of social isolation on depression risk among older adults during COVID-19 in China. Methods Data was obtained from the China Longitudinal Ageing Social Survey (CLASS) conducted in 2020. A total of 9883 participants were included. Depression status was assessed by 9-item Center for Epidemiological Studies Depression Scale (CES-D). Social isolation was assessed by Lubben Social Network Scale-6 (LSNS-6). The odds ratios of depression risk according to LSNS-6 categories were obtained using a logistic regression model with adjustment for potential confounding variables. Results The prevalence of depression was 31.2%, and the presence of social isolation was 37.9% during the COVID-19 among older population. A decrease in depression risk was observed with reduced isolation. The odds ratio for the lowest versus highest was 0.75 (95% confidence interval: 0.63, 0.89; Ptrend = 0.012). Friend support reduced depression risk more significantly than family support. The association between LSNS-6 friend subscale and depression risk was differentiated by LSNS-6 family subscale. In men, LSNS-6 friend subscale tended to be associated with depression risk inversely when their LSNS-6 family subscale was less than 6 (interaction P = 0.041). Similar associations and stratified modifications were observed among those who lived in rural areas (interaction P = 0.002), married (interaction P = 0.003), Han (interaction P = 0.01), lived with others (interaction P = 0.001), and so on. Conclusions Most depression cases were found to be strongly associated with social isolation during the pandemic. Our findings have provided empirical evidence for researchers to understand the association between social isolation and depression, which could help them evaluate and manage depression promptly. Because of the cross-sectional design, we cannot establish causal relationships between depression and isolation.